Investigating India's Progress Toward Digital Authoritarianism: Evidence from Internet Shutdown Amidst Farmer Protest 2024 - Mahayasa, Dias Pabyantara Swandita; Malik, Muhammad Nur Alauddin; Amalia, Dinar Danahari (The Sunan Ampel Review of Political and Social Sciences, 2024)
The notion of economic development often goes hand in hand with political stability. Even in the so-called democratic countries, political stability usually came before democratic value as an underlying reason to keep economic development on track. As one of the biggest democratic countries, India also experiences the paradox. Paradoxically, being one of the digital superpowers with the highest total internet transactions and internet infrastructure, India consistently shown internet shutdowns amidst massive civil protests. Recently, there was a massive farmer protest in February 2024 towards minimum selling prices, which triggered the Indian government to cut off internet access and ban the platform 'X' in several districts in India. Using digital authoritarianism approaches, we argue that the Indian government has claimed digital sovereignty to construct counter-narratives toward the protesters. The strategy was to quell the agitation of the protesters and facilitate the filtering of information amidst massive protests. To investigate the notions, we performed qualitative content analysis upon official social media account of the Indian government. Further, they also target minority groups to limit freedom of information. The Indian government employed such tactics to cover up the atrocities that occurred to prevent attention from the international media. Thus, India does not receive allegations regarding human rights violations